Local nanostructures enhanced the thermoelectric performance of n-PbTe - Xiang, Bo (2022)
Microstructure controlling and carrier concentration engineering are effective approaches to optimize thermal transport and electrical properties in thermoelectric materials. Hereby, we have developed a facile strategy to reduce the lattice thermal conductivity separately by creating locally nanostructured PbTe with controlled size in micro-sized PbTe frame. This is realized by using building blocks of PbTe nanocubes and PbTe@C:Ag nanoparticles with carbon shell as diffusion barrier to prevent grain growth during spark plasma sintering (SPS), while uncoated PbTe nanocubes grow to the micro-sized frame. The locally nano-structured PbTe/PbTe@C:Ag successfully integrates multiple defects that involve Ag based nano-precipitates, nano/micro-sized grain boundaries/interfaces, pores and other defects. They collectively scatter phonons in low-middle frequencies to reduce lattice thermal conductivity significantly in low-temperature range. In addition, Ag exhibits dynamic doping behavior due to more interstitial Ag in PbTe lattice at elevated temperature. This could further enhance the high-frequency phonons scattering and suppress bipolar effect in high-temperature range, leading to an ultralow lattice thermal conductivity of 0.39 W m-1 K-1 at 723 K. On the other hand, the micro-sized PbTe frame with Ag nanoparticles at boundaries maintains relatively high carrier mobility. Further considering the higher carrier concentration due to Ag dynamic doping at elevated temperature, a high power factor of 20.4 μW cm-1 K-2 has been achieved at 723 K. Consequently, a peak figure of merit of 1.65 was achieved at 723K in PbTe/7%PbTe@C:Ag. Our strategy shows superiority in constructing desired nano-, microstructures and tuneable carrier concentration of PbTe towards high thermoelectric performance.